Risk factors associated with drug use before imprisonment in Peru - A Hernández-Vásquez; S Núñez; M Santero; L Grendas; B Huarez; S Vilcarromero; M Casas-Bendezú; S Braun; S Cortés; D Rosselli (Sociedad Española de Sanidad Penitenciaria, 2018)
Abstract Objective To assess the prevalence of drug abuse before prison admission and to identify associated sociodemographic and family history risk factors, according to gender, in prisons of Peru. Materials and methods A secondary analysis was carried out with data from the First National Prisoner Census 2016, using a questionnaire of 173 items that was applied to the whole prison population of Peru. The types of drugs used before admission were analyzed according to characteristics of the penitentiary population, and generalized linear models were used to calculate prevalence ratios with 95% confidence intervals to identify possible factors associated with drug use. Results Out of a population of 76,180 prisoners, 71,184 (93.4%) answered the survey (men 67,071, 94.2%). The overall prevalence of drug consumption before admission was 24.4% (25.3 % in men and 9.1% in women), the highest prevalence in the 18-29 age group (36.3% in men and 14.9% in women). The most commonly used drugs were marijuana (58.2%), coca paste/cocaine or crack (40.3%) and inhalants (1%). The factors most strongly associated with consumption were having a family member who consumed drugs (59.8%), history of previous imprisonment (59.1%), unemployment (48.4%), relationships at school with classmates who had problems with the law (46.9%), background of a family member who attended a penitentiary (38.4%), and history of running away from home before age 15 (35.9%). Conclusions In Peru, drug use is higher in the prison population than in the general population, and there are differences according to sex in the prevalence of drug use and associated factors prior to admission to a prison. The study demonstrated that childhood events, such as child abuse, having a family member imprisoned, having a family member who used drugs, or who previously abused alcohol, are factors associated with drug use in the penitentiary population. Some of these risk factors are modifiable, so it is important to consider these in the design of social and health policies focused on specific subpopulations to prevent drug use and crime.